DAMPAK PROPAGANDA SERIAL DRAMA CRASH LANDING ON YOU TERHADAP HUBUNGAN KOREA SELATAN DAN KOREA UTARA 2020 - Muhammad Rizki Firzani; Putri Ramadhani Harahap (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This Research discuss about Movies or dramas have great influence and can be used as an effective propaganda tool. Lasswell said that propaganda is the control of opinion through meaningful symbols or conveying concrete and accurate opinions through stories. The purpose of this study is to describe the impact of the Film of Korean Drama Crash Landing On You on the relationship between South Korea and North Korea and K-Drama in International Relations especially in the propaganda issue of the Crash Landing On You drama, as well as describing how propaganda can be spread through the Crash Landing On You drama series. By using a method with a qualitative research approach and explanatory research type with sources from books, papers, journals, theses, and articles related to the problems in the research. The result of this study is the impact on Korean relations which is getting worse as a result of the depiction of North Korea in the Crash Landing On You series